A Study Of Braking System Performance On Electric Multiple Unit (EMU) Class 83 - Jaafar, Nurfarahinakmal; Yahya, Musli Nizam; Mohd Ali, Mohd Taufik (Progress in Engineering Application and Technology, 2023)
The braking system’s safety is critical for Electric Multiple Units (EMU). The development of brake systems in railway vehicles was caused by the high safety and comfort expectations under various condition. The main factors influencing brake system performance and function are braking force, vehicle mass and speed, stopping or braking distance, railway condition, and environmental factors. In this work, the types of brake systems such as emergency brakes, parking brakes and service brakes have been reviewed. The study is to analyze failures in the brake system and to propose the action taken to overcome the failure. In this context, data are collected based on the failure on brake system through three – year period from 2020 until 2022. Data collection technique via test run programme of set train and visual inspection. From the analysis, the problems of braking systems were caused by inadequate maintenance and outdated or obsolete braking technology. To reduce the failure of the braking system in trains, several measures can be implemented such as maintaining a strict maintenance schedule, adopting modern braking technology and installing monitoring systems to continuously assess the condition of the braking system during train operations. By addressing these underlying causes, the reliability and safety of train braking systems can be significantly improved.